Determination of the geographical origin of milk based on spectroscopic and chemometric techniques / Shima Behkami - Shima , Behkami (2017)
The Purpose of this research is to develop methods to determine the geographical origin of raw and factory cow milk samples in Peninsular Malaysia and some selected regions of the world. To achieve this, the concentration of mineral and trace elements, isotopic ratio and nutritional values have been studied in this dissertation. We have used various analytical methods have been used for analysis of milk samples such as Inductively Coupled Plasma Mass Spectrometry (ICP-MS), Isotopic Ratio Mass Spectrometry (IRMS), ultrasonic based scanner (Milkoscan), UV/Vis spectrometry and Near Infrared Spectroscopy (NIR). Besides milk, samples of food, pellet, water and plant consumed by cattle as well as rain, soil and cattle hair were also collected from each farm and analyzed in order to observe if there are any possible correlation between these samples and milk. Cattle hair in particular was analyzed with the same procedure as milk samples in order to confirm whether it can be used in place of milk for the determination of geographical origin. The analytical data obtained from these methods were then analyzed using various chemometric methods such as principal component analysis (PCA), hierarchal cluster analysis (HCA), discriminant analysis (DA), Factorial analysis (FA) and artificial neural network (ANN). From the elemental analyses of ICP-MS it is observed that as far as Malaysian raw cow milk samples are concerned, although the separation of samples based on the state where the farms are located is observed, a clearer mapping is ascertained between northern and southern sampling regions. Northern raw cow milk samples are richer in Mo, Al, Mn, Na, Fe, Mg, Zn, Ca, K, Ba, Se and Cu compared to the south where they are mainly loaded with Ni. Malaysian factory milk samples are clustered away from factory milks of some selected countries and the separation is based on the loadings of Ca, Fe, Na, Ba, Zn, Mg, Mn and K. This indicates that Malaysian factory milk samples are richer in these metals compared to factory milks from the selected countries. Multi elemental information on the pellet used in different farms lead to two clusters of pellets which could be explained by the fact that there are only two major factories producing cattle pellets in Peninsular Malaysia. Multi element isotopic analyses of IRMS shows separation of samples in the northern and southern part of Malaysia. The discriminating factors for the southern milk samples are δ18O and δ13C while that of the northern samples is δ15N. Data from milk samples analyzed by NIR and UV/Vis were used to train ANNs and the trained ANNs are able to predict the origin of the milk samples very well. Based on the different analytical and chemometric techniques used in analyzing our samples it can be concluded that even though the chemical and physical variables investigated are different in each method, distinct separation between samples from different geographical origins can be clearly observed.